Tuning photonic bands in plasma metallic photonic crystals - Chaudhari M.K.; Chaudhari S. (My University, 2025)
Introducing plasma in the background provides additional degrees of freedom for tuning dispersion curves of photonic crystals. 2D photonic crystals in triangular lattice arrangements offer more global bandgap regions and thus are of more interest for various applications. The dispersion characteristics of a two-dimensional plasma metallic photonic crystal (PMPC) in square as well as triangular lattice arrangements have been analyzed in this paper using the orthogonal finite difference time domain method. The dispersion characteristics of PMPCs for the range of r/a ratios and plasma frequencies for triangular lattice configuration have been analyzed. On introducing plasma in the background, the photonic bands of PMPC are shifted towards higher normalized frequencies. This shift is more for lower bands and increases with plasma frequency. The cut-off frequency was observed for both TE and TM polarizations in PMPC and showed strong dependence on r/a ratio as well as plasma frequency. Photonic bandgaps of PMPC may be tuned by controlling plasma parameters, giving opportunity for utilizing these PMPC structures for various applications such as fine-tuning cavities for enhanced light-matter interaction, plasmonic waveguides, and Gyrotron cavities. © 2016 Author(s).